1990
DOI: 10.1093/jn/120.6.602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Restriction on the Age-Dependent Changes in the Expression of Antioxidant Enzymes in Rat Liver

Abstract: The effects of aging and dietary restriction on the expression of several enzymes (superoxide dismutase, catalase and glutathione peroxidase) that are involved in free radical detoxification were studied in liver tissue from male Fischer F344 rats. The expression (i.e., activities and mRNA levels) of superoxide dismutase (Cu-Zn) and catalase decreased with age in liver. Dietary restriction (40% restriction of energy intake) increased the activities of superoxide dismutase (24 to 38%) and catalase (64 to 75%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(79 citation statements)
references
References 33 publications
4
71
2
2
Order By: Relevance
“…As it is well known that SOD and catalase act antioxidatively in vivo, 26,32) the elevation of SOD activity in the rats fed with flavonoids may suggest that the ingested flavonoids acted antioxidatively through their action in elevating SOD activity. However, the reason for the lower activity of erythrocytes catalase, in contrast to the higher activity of SOD in the rats fed with the flavonoids, remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is well known that SOD and catalase act antioxidatively in vivo, 26,32) the elevation of SOD activity in the rats fed with flavonoids may suggest that the ingested flavonoids acted antioxidatively through their action in elevating SOD activity. However, the reason for the lower activity of erythrocytes catalase, in contrast to the higher activity of SOD in the rats fed with the flavonoids, remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme solution for determing the catalase activity was prepared according to the method of Rao et al 26 ) The liver tissue (a section from the left lobe, 0.6 g) was homogenized in 4 ml of a buffer containing 0.32 mol sucrose and I mmol EDTA per liter of IOmM Tris-HCI (pH 7.8) in a Teflon-glass homogenizer. The homogenate was centrifuged at 13,600 x g for 30 min at 4°C, and the supernatant obtained was used for the measurement of enzyme activities.…”
Section: Measurement Of the /Ipoperoxide Contentmentioning
confidence: 99%
“…However, the different studies in the literature do not support a clear-cut pattern of CR-related changes in antioxidant defenses, with reports showing controversial effects on these activities (35,42). Differences in rodent model, strain, age of initiation, and duration of CR may be responsible for the differences between these studies.…”
Section: Sexual Dimorphism In Liver Mitochondriamentioning
confidence: 98%
“…However, Rao et al (1990) observed that caloric restriction can attenuate the age dependent decrease of SOD activity. In general, caloric restriction has been observed to increase, decrease, or have no effect on antioxidant enzyme activity in rodents (Koizumi et al 1987;Laganiere and Yu 1989;Rao et al 1990;Feuers et al 1993;Luthala et al 1994).…”
Section: Discussionmentioning
confidence: 99%